Bridging the Development Divide: Promoting Inclusive Economic Policies for Marginalised Women in Pakistan - Rehana Yaqoob*; Muhammad Anwar-Ul-Haq; Naila Parveen Hakro, (Dialogue Social Science Review (DSSR), 2025)
The structural and intersectional hurdles that marginalise poor and rural women are frequently ignored by Pakistan’s economic development policies, despite and increasing governmental focuses on women’s empowerment. This study uses gendered lens to examine the gaps in the social protection and economic development policies that are in place today. The study identifies how structural exclusion, weak institutional integration, and gender- blind policy design perpetuate inequality by using, qualitative research methods, such as document analysis, case studies from women’s protection and rehabilitation Centre’s and thematic coding of policy frameworks like Ehsaas and Vision 2025. The main goals of the study are to assess how well national policies address the vulnerabilities faced by women, investigate institutional shortcomings, and provide intersectional, gender-responsive remedies. The results highlight the pressing need for a comprehensive, revolutionary policy framework that promotes marginalized women’s long-term integration into Pakistan’s economy. Public – private partnerships, intersectional targeting, inclusive policy design, and increased access to digital infrastructure are among the recommendations. Keywords: Inclusive growth, gender-responsive policy, social protection, marginalized women, Pakistan development.